In-vitro assessment of coronary artery stents in 256-multislice computed tomography angiography - André, Florian; Müller, Dirk; Korosoglou, Grigorios; Hosch, Waldemar P.; Kauczor, Hans-Ulrich; Katus, Hugo; Steen, Henning (BMC Research Notes, 2014)
The important detection of in-stent restenosis in cardiovascular computed tomography (CT) is still challenging. The first study assessing the in-vitro stent lumen visualization of the state of the art 256-multislice CT (256-MSCT), which was performed by our research group, yielded promising results. As the applied technical approach is not suitable for daily routine, we assessed the capability of the 256-MSCT and its different reconstruction kernels for the coronary stent lumen visualization employing a clinically applicable technique in a phantom study.
Gesehen am 17.11.2020